2015
DOI: 10.1186/s40488-015-0031-y
|View full text |Cite|
|
Sign up to set email alerts
|

Automatic detection of discordant outliers via the Ueda’s method

Abstract: The importance of identifying outliers in a data set is well known. Although various outlier detection methods have been proposed in order to enable reliable inferences regarding a data set, a simple but less known method has been proposed by Ueda (1996Ueda ( /2009. Since this new method, called Ueda's method, has not been systematically analysed in previous research, a simulation study addressing its performance and robustness is presented. Although the method was derived assuming that the underlying data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In order to ensure that the observed effects were not due to the type of filter used, a multiverse analysis was carried out (Steegen et al, 2016 ). The reaction time filters compared to the one we chose were: 2 median absolute deviations (MAD) and 2 SD per condition for each participant, and no reaction time filter (see Marmolejo-Ramos et al, 2015 , for a discussion of the most appropriate reaction time filters according to the characteristics of the data; see also Marmolejo-Ramos et al, 2015 ). We did not use a logarithmic transformation, because it is problematic when one condition is significantly slower than the other (Lo and Andrews, 2015 ); judgments of valence were much slower than temporal judgements in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…In order to ensure that the observed effects were not due to the type of filter used, a multiverse analysis was carried out (Steegen et al, 2016 ). The reaction time filters compared to the one we chose were: 2 median absolute deviations (MAD) and 2 SD per condition for each participant, and no reaction time filter (see Marmolejo-Ramos et al, 2015 , for a discussion of the most appropriate reaction time filters according to the characteristics of the data; see also Marmolejo-Ramos et al, 2015 ). We did not use a logarithmic transformation, because it is problematic when one condition is significantly slower than the other (Lo and Andrews, 2015 ); judgments of valence were much slower than temporal judgements in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the CLT, HCCM, and bootstrap approaches, trimming and Winsorizing implicitly assume that the observed data are contaminated by the presence of outliers, which are recognized as extreme cases in the tails of the data distribution (e.g., see Tukey and McLaughlin, 1963 ; Wilcox, 2017 ). Barnett and Lewis ( 1998 ) provide an extensive treatment of outliers; and recent work has focused on their automatic detection (e.g., see Mavridis and Moustaki, 2008 ; Marmolejo-Ramos et al, 2015 ). Stated differently, the use of either trimming or Winsorizing presumes that non-normality is due to the presence of improper data, and these erroneous data are discarded or modified.…”
Section: Addressing Non-normality (And Heteroscedasticity)mentioning
confidence: 99%
“…Subsequently, an outlier detection method could be applied to the combined data (i.e., uncontaminated data + outlier observations) and the number of outliers detected would be further compared with that initially introduced. In fact, we have recently found that an outlier detection procedure known as the Ueda's method [53] is more likely to detect outliers when the data's distribution becomes more skewed and asymmetric [54]. Using the Ueda's method for the quantification of outliers affecting distributions transformed via the approach proposed herein is a topic for future investigation.…”
Section: Discussionmentioning
confidence: 98%